The Antecedents of Resource Mobilization by Nascent Entrepreneurs: Team Formation - KOTHA, Reddi Rayalu (Institutional Knowledge at Singapore Management University, 2005)
It has been frequently argued that strong ties are important for mobilization of resources, especially when there is uncertainty on whether the resources will be returned. The empirical evidence of the relationship between strong ties and resource mobilization is equivocal. Further, given that strong ties may not yield instrumental resources, it is puzzling that a majority of nascent ventures form teams with strong tie members. The puzzle is in two parts. First, why do some entrepreneurs select as team members individuals who are less likely to provide resources. Second, strong tie relations are posited to provide resources unilaterally; why then do some entrepreneurs bring strong tie holders within the nascent venture as team members and not others. Including individuals in the nascent teams usually involves giving substantial equity in the nascent venture to such team members. Put differently, why is the focal entrepreneur unable to mobilize resources from strong tie relations without having to give up equity in the nascent venture? I propose that when the human and financial capital of the entrepreneur and the task environment of the startup are considered we can explain i) why some entrepreneurs form teams and not others and ii) why some entrepreneurs select strong tie relations as team members.I plan to test the hypotheses of the study in the PSED database. I use a simultaneous probit model to control for the self-selection of entrepreneurs to form a team and choice of a team member. The paper contributes to theory by making predictions in the various stages of the new venture process on team formation and team member selection. Further, the paper provides normative guidance to entrepreneurs on when to form teams based on the human capital and the context of the new venture.